THE GOTHENBURG MAGNETIC EXCURSION IN THE BLACK SEA SEDIMENTS - Demidenko E.L.; Faustov S.S.; Nikolaev S.D. (My University, 1998)
The late Pleistocene-Holocene deposits are studied in 12 piston-core sections sampled at the continental slope and in the deep part of the Black Sea within the Adler-Tuapse test area. In four of these sections, the Neoeuxinian beds revealed paleomagnetic anomalies confined to the base of the hydrotroilite member1 and presumably induced by the Gothenburg excursion. Correlation with available data on the western region of the Black Sea, where the Gothenburg excursion was first identified, substantiate synchronism of hydrotroilite deposits in eastern and western areas of the sea and elucidate principal trends in the paleogeographic evolution of the Black Sea in the late Pleistocene-Holocene time.
Keywords: Holocene; Pleistocene; Кайнозой::Четвертичная::Голоцен; Cenozoic::Quaternary::Pleistocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Плейстоцен